WAC and Second-Language Writers Research Towards Linguistically and Culturally Inclusive Programs and Practices - Zawacki, Terry Myers; Cox, Michelle (Open textbook library., 2014)
In WAC and Second-Language Writers, the editors and contributors pursue the ambitious goal of including within WAC theory, research, and practice the differing perspectives, educational experiences, and voices of second-language writers. The chapters within this collection not only report new research but also share a wealth of pedagogical, curricular, and programmatic practices relevant to second-language writers. Representing a range of institutional perspectives—including those of students and faculty at public universities, community colleges, liberal arts colleges, and English-language schools—and a diverse set of geographical and cultural contexts, the editors and contributors report on work taking place in the United States, Asia, Europe, and the Middle East.